Analisis Penggunaan Lampu Lalu Lintas Pada Persimpangan Jalan Imam Bonjol Dengan Jalan Suprapto Kota Palangka Raya Dengan Menggunakan Metode MKJI - Nirwana Puspasari; Parsi Sahara (Anterior Jurnal, 2015)
The better of society welfare makes the development rate of traffic as a means transportation is increasing as well. On the crossroad of Suprapto and Imam Bonjol street in Palangka Raya city, traffic conflicts often happened there due to the flow of traffic at the intersection is quite crowd in the morning, afternoon and evening. This study was conducted to analyze the performance of intersection by using MKJI done by comparing the time of red, green and circle time with the analysis results due to the changes in volume today. By using MKJI method, the variable is the size of the city, geometric, direction of flow, volume, velocity and phase. The results of the field survey dan the result of the analysis so the level of service and utilization of signal light at Suprapto – Imam Bonjol is good enough, but for the using of traffic light at the intersection is still needed because of the degree of saturation (DS) on pendekat North = 0.618, Pendekat West = 0.635 and Pendekat East = 0.364 which still meets the standard value of Degree of Saturation, that is ≤ 0.85 with an average delay of 2.83 sec/smp, and it means that the crossroad did not have traffic jams during rush hour. At this crossroad, it does not need any setting with traffic lights, but it is enough to be paired in median only.